2021
DOI: 10.1055/s-0040-1722346
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Arm-Assisted Lateral Unicompartmental Knee Arthroplasty: How Are Components Aligned?

Abstract: The purpose of this multicenter, retrospective, observational study was to investigate the association between intraoperative component positioning and soft tissue balancing, as reported by robotic technology for a cohort of patients who received robotic arm-assisted lateral unicompartmental knee arthroplasty (UKA) as well as short-term clinical follow-up of these patients. Between 2013 and 2016, 78 patients (79 knees) underwent robotic arm-assisted lateral UKAs at two centers. Pre- and postoperatively, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Authors reported that lateral RA-UKA was associated with a significantly quicker return to sports compared with the conventional technique (4.2 ± 1.8 months vs. 10.5 ± 6.7 months). Favourable outcomes with the utilisation of robotic-arm assistance in lateral UKA have been reported by several other studies (35)(36)(37)(38)(39)(40), showcasing the positive impact of precise bone cuts and accurate implant positioning.…”
Section: Discussionmentioning
confidence: 68%
“…Authors reported that lateral RA-UKA was associated with a significantly quicker return to sports compared with the conventional technique (4.2 ± 1.8 months vs. 10.5 ± 6.7 months). Favourable outcomes with the utilisation of robotic-arm assistance in lateral UKA have been reported by several other studies (35)(36)(37)(38)(39)(40), showcasing the positive impact of precise bone cuts and accurate implant positioning.…”
Section: Discussionmentioning
confidence: 68%
“…pain, mild stiffness, subjective dysfunction, or any discomfort [3]. FJS-12 has been introduced in different joint related studies [4][5][6][7][8][9][10] together with some "gold standards", such as Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) [11,12], Oxford Knee Score (OKS) [13], Knee Injury and Osteoarthritis Outcome Score (KOOS) [14], Knee Society Score (KSS) and Function Score (KFS) [15]. Recent technology allows patients to look for the information concerning their disease symptoms, treatments receiving and expected outcomes.…”
Section: Introductionmentioning
confidence: 99%